Life course social connectedness : age-cohort trends in social participation - Ang, Shannon (2020)
Social connectedness has emerged in recent decades as a key determinant of well-being. Considering its importance, several studies have sought to describe how overall trends in society have changed over the years, while others have been more concerned with how it changes as individuals age. This study set out to synthesize these two strands of research by describing age-cohort trends of social connectedness, using social participation as the key indicator. Data are from the Americans’ Changing Lives survey, a nationally representative panel dataset with an accelerated longitudinal design, collected over 25 years. Multivariate Bayesian generalized additive mixed models (GAMMs) were utilized to estimate age-cohort trajectories of formal and informal social participation. Findings show that even as informal social participation decreases with age, formal social participation increases – suggesting some form of compensatory mechanism. Further, while informal social participation remains stable across cohorts, formal social participation increases in later cohorts. These results suggest that the isolation of old age or overall societal declines in social participation in America may be overestimated by some observers, but more research is needed to more comprehensively describe how other aspects of social connectedness are distributed over the life course.